Lithium compounds for thermochemical energy storage: A state-of-the-art review and future trends. (October 2021) - Marín, P.E.; Milian, Y.; Ushak, S.; Cabeza, L.F.; Grágeda, M.; Shire, G.S.F.
Abstract: The world is currently going through significant changes in technology, and alongside these advances, new developments of strategies to store and supply energy are crucial for the widespread use of consumer electronics and white goods. Besides, the impacts of greenhouse gas emissions and climate change are exerting pressure towards less polluting sources of energy and strategies to diminish energy losses. In this environmental context, lithium compounds are an attractive alternative to store energy in thermal energy storage systems due to their thermodynamic features, which make such compounds a relevant strategy for energy storage, for instance, capturing residual energy from several industrial activities. Here a review of the current state of the art and new technological advances reflected by the scientific literature and the patented inventions using lithium as a relevant compound for thermochemical energy storage has been performed. Throughout a search on different databases, it is proposed a simplified process to support our findings and the analysis of this data. Thus, several important advances in thermochemical energy storage using chemical reaction and sorption systems were evidenced. The literature also showed that the majority of the analysed investigation included in our data set are based on sorption technologies. This review suggests the need for systematisation in reporting critical data to facilitate a common understanding with regards to the advances in energy storage, especially when referring to heat storage density. The importance of lithium in thermochemical systems in the future will probably keep increasing, particularly in systems where several lithium salts have shown to be excellent doping agents and working pairs of materials included in different matrices. Highlights: Lithium materials for thermochemical energy storage dominated by sorption technologies. Lithium salts have shown to be excellent doping agents and working pairs. Improved conductivity and permeability by matrices on Lithium based systems. Important parameters; enthalpy, activation energy, energy storage density. Commercial patents are dominated by sorption technologies using Lithium bromide.